Design and Evaluation of Double-Stage Energy Harvesting Floor Tile - Don Isarakorn; Subhawat Jayasvasti; Phosy Panthongsy; Pattanaphong Janphuang; Kazuhiko Hamamoto (My University, 2019)
This paper introduces the design and characterization of a double-stage energy harvesting floor tile that uses a piezoelectric cantilever to generate electricity from human footsteps. A frequency up-conversion principle, in the form of an overshooting piezoelectric cantilever, plucked with a proof mass is utilized to increase energy conversion efficiency. The overshoot of the proof mass is implemented by a mechanical impact between a moving cover plate and a stopper to prevent damage to the plucked piezoelectric element. In an experiment, the piezoelectric cantilever of a floor tile prototype was excited by a pneumatic actuator that simulated human footsteps. The key parameters affecting the electrical power and energy outputs were investigated by actuating the prototype with a few kinds of excitation input. It was found that, when actuated by a single simulated footstep, the prototype was able to produce electrical power and energy in two stages. The cantilever resonated at a frequency of 14.08 Hz. The output electricity was directly proportional to the acceleration of the moving cover plate and the gap between the cover plate and the stopper. An average power of 0.82 mW and a total energy of 2.40 mJ were obtained at an acceleration of 0.93 g and a gap of 4 mm. The prototype had a simple structure and was able to operate over a wide range of frequencies.
Keywords: Proof mass; Mechanical energy; Overshoot (microwave communication); Innovative Energy Harvesting Technologies